EVALUATION OF REPRESENTATIVENESS OF SAMPLES USED FOR INDOOR RADON SURVEYS. Issue 2 (30th October 2020) - Caprio, M; Venoso, G; Ampollini, M; Antignani, S; Carpentieri, C; Di Carlo, C; Pozzi, S; Carelli, V; Cordedda, C; Bottacchiari, F; Bochicchio, F
Abstract: The estimation of the indoor radon exposure of the population of a country is generally carried out by the means of surveys designed in order to have sample representativeness as a target (population-based survey). However, the estimates of radon concentration distributions could be affected by biases if sampling was not random or in case of differences between sample and target population characteristics. In this work, we performed a preliminary check of the representativeness of the sample used for the second Italian national survey aimed to evaluate radon concentration distribution in each Province. We found that sampled dwellings are mostly located in the main administrative centres, where average radon concentration is generally lower, as compared with the other towns of the Province. The potential source of bias identified in this work suggests to carefully control the occurrence of a sampling imbalance between 'main' cities and other cities of Province and to take it into account in data analysis.